Health behavior and health needs of first-year medical and health sciences students - GÜR, KAMER; EROL, SAİME; ÇİFÇİLİ, SALİHA SERAP; ÇALIK, KEVSER BURCU; YILDIZ ÖZER, AYSEL; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN; APAYDIN KAYA, MEMNUNE ÇİĞDEM (My University, 2023)
ABSTRACT Objective: The aim of this study is to evaluate the health behavior and health needs of medical and health sciences students in order to identify areas that need intervention. Materials and Methods: This descriptive study was conducted with 770 first-year university students. The data were collected with a sociodemographic questionnaire, the Youth Risk Behavior Survey and the Eating Attitudes Test. Body mass index was calculated. Results: Although, only 12.7% of the students were overweight or obese, 25.6% of the students perceived themselves to be overweight or obese. The students said that in the last week, 20.9% had breakfast 1 or 3 times, 5.7% ate no fruits at all, and 11.6% ate no vegetables at all. 48.1% of the students did not engage in any physical activity, and 83.2% spent more than 2 hours inactively in front of a screen. It was observed that 22.3% were current smokers. A propensity for eating behaviors disorder was found in 9.0%. Drinking energyboosting sports drinks 1-6 times in the last week (β: 3.286), smoking (β: 1.875) and eating few vegetable dishes in the last week (β: 0.484) were identified as factors that could be associated with a “tendency for eating behavior disorder.” Conclusion: We can conclude that nutritional issues, negative body weight perception, use of tobacco, and sedentary lifestyle are the main intervention and counselling areas for our study group.
Keywords: Health behavior; Health needs; Medical students; Health sciences